The effect of entomopathogenic nematodes and fungi against four xylophagous pests. Issue 9 (1st September 2020) - El Khoury, Yara; Noujeim, Elise; Ravlić, Josip; Oreste, Monica; Addante, Rocco; Nemer, Nabil; Tarasco, Eustachio
ABSTRACT: The effects of entomopathogenic nematodes EPN (Steinernematidae and Heterorhabditidae) and fungi EPF ( Beauveria bassiana ) strains were evaluated in laboratory assays against larvae of four xylophagous pests: the Asparagus moth Parahypopta caestrum, the European goat moth Cossus cossus, the pine longhorn Arhopalus syriacus and the black Buprestid Capnodis tenebrionis. Due to their biology and ethology, these insects may be included in the category of pests residing in cryptic habitats. The control of these species is considered difficult, due to the inability of chemical pesticides to penetrate the cryptic habitats and reach the targets. The pathogenicity of the entomopathogenic nematodes and fungi was tested in vitro against the pests. Two experimental models were considered and aimed to imitate the natural environment of the pests, in Petri dishes filled with plant material and inside wood galleries respectively. Main results showed that the majority of the tested strains of nematodes and fungi affected the insects' survival rate. Steinernema feltiae and B. bassiana caused the highest percentage of larval mortality (80–100%). Considering the lack of effective chemical control means, the microbial control of the xylophagous pests by EPN and EPF reveals promising perspectives. Nematodes and fungi are able to penetrate the cryptic habitats because they are living organisms and may be horizontally transmitted by infected hosts. The distribution of EPF as preventive control method and the injection of EPN suspensions to reach and infect the larvae inside the wood galleries can be a combined sustainable control system.